1978
DOI: 10.1139/v78-305
|View full text |Cite
|
Sign up to set email alerts
|

Synthèse et caractérisation des oxypentafluorouranates(VI) NH4UOF5, KUOF5, RbUOF5 et CsUOF5

Abstract: Chem. 56,1874Chem. 56, (1978.The oxypentafluoroirranates(V1) MUOF,, where M = NH,, K , R b , Cs, have been synthetized from reaction of UOF, with the animoniu~n or corresponding alkali metal fluoride in liquid SO,. According to X-ray diffraction, Raman and infrared spectroscopy, and from an isoniorphism with the corresponding hexafluorouranates(V) MUFG, two different environ~nents around the ilranii~m atom are observed. In CsUOF, the five fluorine atoms a n d the oxygen around the i~ranium result in a pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…2). This is in full agreement with the vibrational spectroscopy study ( 3 ) from which it was concluded that the UOF,-ion has the C , , point group symmetry. On the other hand the force constant calculation has shown the axial fluorine atom (trans to the oxygen atom) to be less ionic in character than the equatorial fluorine atoms.…”
Section: I9f Broad Line Nuclear Magnetic Resonancesupporting
confidence: 90%
See 3 more Smart Citations
“…2). This is in full agreement with the vibrational spectroscopy study ( 3 ) from which it was concluded that the UOF,-ion has the C , , point group symmetry. On the other hand the force constant calculation has shown the axial fluorine atom (trans to the oxygen atom) to be less ionic in character than the equatorial fluorine atoms.…”
Section: I9f Broad Line Nuclear Magnetic Resonancesupporting
confidence: 90%
“…The synthesis and characterization of the oxypentafluorouranates(VI) of monovalent cations MUOFj (where M = NO, NH,, K, Rb, Cs) have been described previously (1)(2)(3). According to these studies, a~nollg the alkaline metals studied only CsUOF, has been found to contain the UOF,-ion.…”
Section: Lntrodnctionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these the two most favored uranyl coordinations are [UO 2 F 5 ] 3-, corresponding to a uranyl unit coordinated by five fluorine atoms in the equatorial plane, or [UO 2 F 4 O] 4-, a uranyl pentagonal bipyramid coordinated in the equatorial plane by four fluorine atoms and one oxygen atom. Various uranyl oxy-fluoride inorganic compounds [39][40][41][42] and minerals [43,44] have also been described in the literature. In these compounds it is common for the uranyl unit to have a variable ratio of oxygen to fluorine atoms in the equatorial plane of bypiramids such as [UO 2 being part of the uranyl tungstate sheet.…”
Section: Discussionmentioning
confidence: 99%